Do reparations repair relationships?: Setting the stage for reconciliation in Colombia - Firchow, Pamina (International journal of transitional justice, 2017)
Colombia is groundbreaking in its approach of prioritizing victim involvement and participation in its peace process and including victims in peace agreement discussions in Havana. Colombia started this process with an ambitious reparations law, which aims to individually and collectively compensate almost 8.3 million victims in order to begin a reconciliation process. Yet the link between reparations and reconciliation is inconclusive. This study looks at the impact of reparations on reconciliation through a comparative matched-case research study of two Colombian communities that are demographically similar and have similar histories of violence, but starkly different levels of reparations. The study employs a participatory methodological approach using inductive indicators of peace and reconciliation created by the communities themselves in order to create surveys that measure the impact of reparations on reconciliation. The study finds that both communities display low levels of reconciliation according to community-defined indicators, and that there is little variance between the two villages in the way the community members define peace and reconciliation and in the levels of community-defined peace and reconciliation in each community. Based on these findings, the article concludes with four recommendations for more comprehensive and effective implementation of reparations programs in war-affected communities.